1989
DOI: 10.1159/000261155
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Dental Caries in an Adult Rural Population

Abstract: A study was conducted amongst 1,131 randomly selected persons aged 15–65 years in a rural area of Kenya, having minimal access to dental care. A relatively low prevalence of frank cavitation was found in the 15- to 24-year-old cohort, but in the older age groups over 80% were so affected. Caries in the youngest cohort was characterized by a predominance of enamel lesions. At the age of 25–34 years, however, involvement of pulpal tissues and loss of teeth due to caries was more common, and this age group exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 13 publications
3
50
1
1
Order By: Relevance
“…As this considerably hampers attempts to identify the causes of caries lesion initiation, we prefer to include the non-cavitated stages in the diagnostic system [Gadegaard and Fejerskov, 1983;Manji et al, 1989] to obtain more valid estimates of prevalence and severity of the disease [Groeneveld, 1985;Manji et al, 1991]. It is noteworthy that this is now also being considered as very important when attempting to develop appropriate prevention and treatment strategies for child populations [Pitts and Fyffe, 1988;Ismail et al, 1992Ismail et al, , 1997Pitts, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…As this considerably hampers attempts to identify the causes of caries lesion initiation, we prefer to include the non-cavitated stages in the diagnostic system [Gadegaard and Fejerskov, 1983;Manji et al, 1989] to obtain more valid estimates of prevalence and severity of the disease [Groeneveld, 1985;Manji et al, 1991]. It is noteworthy that this is now also being considered as very important when attempting to develop appropriate prevention and treatment strategies for child populations [Pitts and Fyffe, 1988;Ismail et al, 1992Ismail et al, , 1997Pitts, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…been shown that diagnosis of caries at the cavitation level results in a significant underestimation of the actual caries experience in populations [Pitts and Fyffe, 1988;Manji et al, 1989;Ismail et al, 1992;Bjarnason et al, 1993;Kuzmina et al, 1995;Sköld et al, 1995;Machiulskiene et al, 1998]. …”
mentioning
confidence: 99%
“…The dental caries of children were recorded by disposable mouth mirror and dental explorer. The diagnosis of dental caries was carried out according to the criteria of Manji et al [12]. This allows recording decayed lesion by severity.…”
Section: Methodsmentioning
confidence: 99%